2016
DOI: 10.1002/2016gl069416
|View full text |Cite
|
Sign up to set email alerts
|

High atmospheric demand for water can limit forest carbon uptake and transpiration as severely as dry soil

Abstract: When stressed by low soil water content (SWC) or high vapor pressure deficit (VPD), plants close stomata, reducing transpiration and photosynthesis. However, it has historically been difficult to disentangle the magnitudes of VPD compared to SWC limitations on ecosystem‐scale fluxes. We used a 13 year record of eddy covariance measurements from a forest in south central Indiana, USA, to quantify how transpiration and photosynthesis respond to fluctuations in VPD versus SWC. High VPD and low SWC both explained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
153
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 214 publications
(166 citation statements)
references
References 63 publications
10
153
3
Order By: Relevance
“…Such synoptic conditions are the most common weather pattern associated with Australian heat waves (Steffen et al, 2014). However, these weather patterns did not result in increased amounts of available energy at the surface, which was in contrast to heat waves observed in Europe and the USA (see Sect.…”
Section: Consequences Of Australian Heat Waves On Energy Fluxesmentioning
confidence: 57%
See 3 more Smart Citations
“…Such synoptic conditions are the most common weather pattern associated with Australian heat waves (Steffen et al, 2014). However, these weather patterns did not result in increased amounts of available energy at the surface, which was in contrast to heat waves observed in Europe and the USA (see Sect.…”
Section: Consequences Of Australian Heat Waves On Energy Fluxesmentioning
confidence: 57%
“…identified an increased vapour pressure deficit as detrimental to transpiration and net carbon uptake, finding that increased vapour pressure deficit is more detrimental than increased temperatures alone -with or without the imposition of drought. A recent study by Sulman et al (2016) confirmed that episodes of elevated vapour pressure deficit could reduce carbon uptake regardless of changes in soil moisture. Here, all ecosystems responded with increased carbon uptake to the precipitation events and the associated lower temperatures and vapour pressure deficit.…”
Section: The Effect Of Intermittent Precipitation During the Heat Wavementioning
confidence: 81%
See 2 more Smart Citations
“…The water saving benefits to plants of high CO 2 have the potential to counteract high temperature and VPD which occur during drought events [69]. However, while these effects are likely to be helpful during baseline or average conditions [70][71][72], but may not be able to compensate during extreme events (e.g. [73]).…”
Section: Plant Stress Under "Hot" Droughtsmentioning
confidence: 99%